Vitamin D receptor gene variants contribute to hip and knee osteoarthritis susceptibility - Vranić, Vladimir; Zeljić, Katarina; Štefik, Debora; Ivković, Nemanja; Abazović, Džihan; Arsenijević, Nebojša; Vojvodić, Danilo; Šupić, Gordana (Archives of Biological Sciences, 2021)
Paper description: Vitamin D receptor (VDR) gene polymorphisms could play a significant role in susceptibility to osteoarthritis (OA), the most common degenerative joint disorder in humans. VDR gene variants FokI, TaqI, ApaI and EcoRV were genotyped using TaqMan based Real-Time PCR in 94 OA patients and 100 healthy controls. VDR FokI and TaqI genetic variants contribute to osteoarthritis susceptibility, occurrence of persistent pain and potentially to joint-specific OA risk. Future directions could include supplementation according to VDR polymorphisms and serum vitamin D status to potentially delay OA onset, slow down its progression and reduce pain in OA patients. Abstract: Vitamin D receptor (VDR) gene polymorphisms could play a significant role in the susceptibility and pathogenesis of osteoarthritis (OA), the most common degenerative joint disorder in humans. The current study involved 94 OA patients and 100 healthy, asymptomatic controls. VDR variants FokI (rs2228570), TaqI (rs731236), ApaI (rs7975232) and EcoRV (rs4516035) were genotyped using TaqMan-based real-time PCR. Adjusted odds ratio (OR) analysis showed that VDR TaqI and FokI polymorphisms are significantly associated with susceptibility to OA (OR=1.986, P=0.001 and OR=1.561, P=0.017, respectively). Joint-specific analysis showed that the VDR TaqI polymorphism was associated with risk of hip OA (OR=1.930, P=0.005) and knee OA (OR=1.916, P=0.028), while the VDR FokI polymorphism was associated with higher risk of knee OA (OR=2.117, P=0.012). VDR TaqI and FokI polymorphisms are associated with the occurrence of persistent pain (P=0.005 and P=0.027, respectively), while ApaI was associated with a family history of OA (p=0.004). The VDR FokI and TaqI genetic variants significantly contribute to osteoarthritis susceptibility, the occurrence of persistent pain, and potentially to joint-specific OA risk.